1987
DOI: 10.1111/j.1423-0410.1987.tb05069.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Storage Lesion in Second‐Generation Containers: Correlation with Platelet ATP Levels

Abstract: The nature of platelet lesion occurring with storage of platelet concentrates (PC) in second-generation containers was investigated using various storage media and storage periods up to 14 days. In CPD-plasma (control medium), the changes which occurred progressively during storage were loss of discoid shape, microscopic platelet aggregate formation, fragmentation and the appearance of disintegrated, 'balloon' forms. By day 14 less than 10% of the platelets were discoid in shape, the platelet count had decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 33 publications
11
71
0
Order By: Relevance
“…This close correlation between the aspects of the storage lesion and loss of metabolic activity was confirmed in the recently published results of Holme (34) showing the correlation between metabolic activity, ATP concentration and storage lesion.…”
Section: Csupporting
confidence: 72%
“…This close correlation between the aspects of the storage lesion and loss of metabolic activity was confirmed in the recently published results of Holme (34) showing the correlation between metabolic activity, ATP concentration and storage lesion.…”
Section: Csupporting
confidence: 72%
“…ACD in contrast to CPD does not contain phosphate and is routinely used for the preparation of apheresis platelets. Effects similar to those observed in the absence of glucose during storage of platelets [1,21,22] have been observed in PCs prepared by apheresis [16]. These effects may be associated with the use of ACD solution in combination with the nonphosphate-additive solution PAS-2.…”
Section: Effects Of Phosphatementioning
confidence: 53%
“…The 'endogenous fuel' acting as a major substrate can be fatty acids [20]. On the other hand, depletion of glucose and, in the next step, significantly reduced levels of adenine nucleotides have been associated with loss of platelet viability [1,21,22]. In a study by Klinger et al [23] focusing on morphological changes, PCs prepared by apheresis were stored in either plasma or PAS-2 with a very limited plasma carryover (10%).…”
Section: Effects Of Glucosementioning
confidence: 99%
“…As PAS contains 27 mM of acetate, this suggests maintenance of platelet viability for $13 days of storage as our studies demonstrated. Some studies have suggested that enough plasma must be present during platelet storage to maintain glucose levels, 35,36 whereas others have indicated that residual glucose is not required. 37,38 Our studies have indicated that, depending on the storage conditions (mainly the storage bag), acetate can substitute for glucose to maintain platelet viability.…”
Section: Discussionmentioning
confidence: 99%